Português e cultura por meio da música brasileira: o ensino para imigrantes e refugiados - Braciak, Patrícia (2024)
Learning Portuguese is essential for immigrants' social and economic integration in Brazil, enabling communication, citizenship, interculturality, and integration into Brazilian society. This article discusses the didactic sequence (DS) as a model for planning Portuguese as an Additional and Welcome Language (PLAAc) class. Based on Sociodiscursive Interactionism, this qualitative, bibliographic, and exploratory research is justified by the need to create specific teaching materials that meet the demands of students. It presents the DS proposed by Dolz, Noverraz, and Schneuwly (2004) and bases its theoretical foundation on authors such as Bakhtin (2006; 2010) and Schlatter (2009). We consider the potential of Brazilian popular music (MPB) as an authentic, integrative genre that promotes engagement and motivation for using the language in the classroom. The results indicate that the DS is effective as a planning model by enabling the understanding of the genre, the organization of activities, and the progression of knowledge. The study reinforces that the didacticisation of music favors teaching when integrated as a pedagogical resource while promoting interculturality and the exchange of experiences.